Reshaping the Business Incubator Model: The Case of the Value Chain Model of Innovation Works in China. (November 2019) - Tang, Mingfeng; Li, Cuiwen; Baskaran, Angathevar; Cheng, Yu; Chandran, VGR
Since the late 1980s, the business incubator model in China has been evolving—from the early traditional model that focused mainly on providing basic services, such as office space and one-stop administrative services, to an emerging value chain model (value position, value creation, value transfer and value capture), which efficiently combines the profits of an incubator with the success of its incubating tenant ventures. This article analyses the case of 'Innovation Works', which is one of the pioneers of the value chain model in China. It raises the following research questions: (a) how does the incubator business model evolve over time in China? (b) What differentiates the value chain business incubator model from the traditional model? (c) What are the critical elements that contribute to the success of a value chain business incubator model? Using primary data gathered through interviews, on-site visits and surveys, the study found that the incubator business model in China has been reshaping towards more complex value propositions and more efficient value chain models. The study also found that specialisation, flat organisational structure and professional management team are the critical elements that contribute to the success or efficient performance of the value chain business incubator model. This article makes significant contributions to the literature and draws policy implications for future business incubator development—both in China and in other emerging economies.